Recurrent Extreme Climatic Events Are Driving Gorgonian Populations to Local Extinction Low Adaptive Potential to Marine Heatwaves - Ramirez-Calero, Sandra (Global change biology, 2024)
© 2024 The Author(s). Global Change Biology published by John Wiley & Sons Ltd.